The Kinetic Effects on Thymidine Kinase 2 by Enzyme-Bound dTTP May Explain the Mitochondrial Side Effects of Antiviral Thymidine Analogs - Wang, Liya (American Society for Microbiology, 2011)
Mitochondrial thymidine kinase 2 (TK2) is a key enzyme in the salvage of pyrimidine deoxynucleosides needed for mitochondrial DNA synthesis. TK2 phosphorylates thymidine (dThd), deoxycytidine (dCyd), and many other antiviral pyrimidine nucleoside analogs. Zidovudine (AZT) is the first nucleoside analog approved for anti-HIV therapy, and it is still used in combination with other drugs. One of the side effects of long-term treatment with nucleoside analogs is mitochondrial DNA depletion, which has been ascribed to competition by AZT for the endogenous dThd phosphorylation carried out by TK2. Here we studied the kinetics of AZT and 3′-fluorothymidine phosphorylation by recombinant human TK2 and the effects of these and other pyrimidine nucleoside analogs on the phosphorylation of dThd and dCyd. Thymidine analogs strongly inhibited dThd phosphorylation but not dCyd phosphorylation, which instead was stimulated ∼30%. We found that recombinant human TK2 contained the feedback inhibitor dTTP in a 1:1 molar ratio and that incubation with dThd and AZT could completely remove the enzyme-bound dTTP, but dCyd was less efficient in this regard. The release of feedback inhibitor by dThd and dThd analogs most likely accounts for the observed kinetics. Similar effects were also observed with native rat liver mitochondrial TK2, strongly indicating a physiologic role for this process, which most likely is an important factor in the mitochondrial toxicity observed with antiviral nucleoside analogs.